Soft Target : How the Indian Intelligence Service Penetrated Canada - Kashmeri, Zuhair and McAndrew, Brian (Toronto James Lorimer and Company, 1989)
On March 16, 2005, almost twenty years after one of the biggest mass murders in Canadian Aviation history, the Air-India Case concluded with a verdict that authors Zuhair Kashmeri and Brian McAndrew predicted sixteen years ago when Soft Target was first published.
Include Colour Illustration and Index
Keywords: Terrorism -- Canada -- India -- Sikhs--Politics and government -- India--Punjab -- Politics and government -- India. Intelligence Bureau